Aetiology and Outcome of Acute Kidney Injury Patients at the Nephrology Unit of Pak Emirats Military Hospital Rawalpindi - Ali, Asif; Azam Khan, Malik Nadeem; Ali, Imran; Hussain, Muhammad Zahid; Khan, Muhammad Shahid; Sajid, Yasmeen (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the aetiology and outcome of patients admitted with acute kidney injury at the Nephrology Unit of Pak Emirates Military Hospital (PEMH).Study Design: Cross-sectional analytical study.Place and Duration of Study: Nephrology Unit, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Jun 2019 to Jun 2020.Methodology: Patients admitted with AKI were included in the study. The Kidney Disease: Improving Global Outcomes(KDIGO) clinical practice guidelines were used to diagnose acute renal injury based on creatinine level or urine output. Results: A total of 300 patients were admitted to the Nephrology Unit with AKI during the study period. Sepsis was the commonest aetiology for acute kidney injury among the target population, followed by injury. 155(51.4%) patients were discharged, 53(17.7%) were stable in the ward, 70(23.4%) patients were shifted to the Critical Care Unit, and 22(7.3%) died.Long duration of hospital stay and the presence of multiorgan failure had a statistically significant relationship with poor outcomes in our study.Conclusion: This study gives an insight into the aetiology and outcome of acute kidney injury among acute kidney injury patients admitted to the nephrology ward. Sepsis and injury were the commonest causes affecting renal function. Most of the patients had a good outcome. Patients with long hospital stays and multiorgan failure should be given special attention as they were more at risk of poor outcomes in our study.